Knowledge, awareness, attitude and practice of dental practitioners regarding Covid-19 pandemic and infection control: a cross sectional study in Kolkata metropolitan region - Ritwika Bera; Preeti Kalia; Shilpa Hiremath; Deepesh Jaiswal (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Coronavirus disease 2019 (COVID-19) is a global pandemic with more than 53,973 people affected in West Bengal state of India. Objectives. The aim of present study was to assess the Knowledge, Attitudes and Practices (KAP) of dental practitioners in Kolkata city, West Bengal, India regarding COVID-2019 pandemic. Materials and method. Online questionnaire was distributed among dentists across West Bengal city, using a combination of convenience and snowball sampling. The questionnaire had 17 questions: (1) Section A was 'General section' which comprised of socio-demographic and professional details of the subjects; and (2) Section B comprised of 14 questions depicting knowledge, awareness attitude and practice regarding COVID-19. The data collected was subjected to statistical analysis with level of significance at p=0.05. The descriptive statistical analysis was done to compute frequency and percentages. Intergroup comparison was determined by Chi-square statistical analysis to determine the level of significance for responses of each question. Results. Around 70.4% undergraduates participated in the study. Only 4.3% showed accurate knowledge with respect to the incubation period of coronavirus. Coughing and sneezing was considered to be the most common mode of transmission. 98.9% of dentists considered fever to be the characteristic symptom of the disease. Hand washing and alcohol rubs was advocated by 99.5% of the dentist. Emergency procedures were considered necessary by 90.8% dentists. 75.1% of dentists agree that their practice has been affected by the pandemic. Conclusion. A constant update regarding COVID-19 should be made available to dental health care professionals through webinars, seminars, discussions and articles. Dentists should keep themselves updated and help to fight against this pandemic.